Living Donor Liver Transplantation for Hepatic Venoocclusive Disease/Sinusoidal Obstruction Syndrome Originating from Hematopoietic Stem Cell Transplantation. (21st May 2022) - Ichimura, Kentaro; Kawamura, Norio; Goto, Ryoichi; Watanabe, Masaaki; Ganchiku, Yoshikazu; Shimamura, Tsuyoshi; Taketomi, Akinobu
Abstract : Background . Venoocclusive disease (VOD), also known as sinusoidal obstruction syndrome (SOS), is a life-threatening hematopoietic stem cell transplantation (HSCT) complication. Cases of mild and moderate VOD/SOS are self-limiting; however, the mortality for severe VOD/SOS has reached 80%. Recently, defibrotide became available and has been used for VOD/SOS; however, the outcome for patients with severe VOD/SOS is not satisfactory, and liver transplantation is attempted in these severe cases. Method . We describe a case of living donor liver transplantation (LDLT) for acute liver failure secondary to VOD/SOS that originates from HSCT. Result . Liver regeneration after LDLT was impaired, and several infections were developed before liver regeneration completion. Our patient suffered sepsis and finally died of multiorgan failure. Conclusion . Severe VOD/SOS originating from HSCT is associated with a very poor prognosis. The liver transplantation outcome for VOD/SOS has not been satisfied, but it may provide long-term survival if successful. We considered liver transplantation as a therapeutic option, especially in cases where sufficient graft volume is secured, considering impaired liver regeneration under bone marrow suppression after HSCT.